Dramaturgical Nature of Everyday Discourse: A Strategic Approach - N. N. Beloshitskaya (Научный диалог)
This study explores the phenomenon of the dramaturgical nature of everyday discourse. The dramaturgical aspect of discourse is examined as a planned construct, generated through the efforts of interactional subjects. It is posited that in ordinary reality, linguistic individuals recognize the presence of scripted norms when they are violated. To analyze this phenomenon, genres that emphasize the form of expression were selected, including playful exchanges of insults, witty remarks, social conversation, and compliments. The illustrative material consists of instances of everyday discourse found in literary texts from the Russian National Corpus. The search was conducted using lexical units that denote actions, forms of action execution, and titles of the chosen genres: “courteously,” “socially,” “social conversation,” “joke,” and “to joke.” The overall corpus of linguistic material comprised 91 textual excerpts. A pragmatic-linguistic, discursive, and componential analysis was performed. It was revealed that the most frequent tactic in strategically constructing dramaturgical elements is the choice of tonality, as tonality sets interpretative frameworks. The analysis indicated that the emphasis on the form of expression, as an instance of linguistic creativity in implementing dramaturgical strategies, is accompanied by the conventionalization of communicative moves, which acquire symbolic functions.